THE AKUSHA-DARGO FEDERATION AND KAZIKUMUKH SHAMKHALATE: A MUTUALLY BENEFICIAL ALLIANCE IN HISTORICAL CONTEXT - Murtazaev, Arsen Omarovic; Aliev, Bagomed Gadaevic (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines the historical relationship between the Akusha-Dargo federation of unions and the Kazikumukh Shamkhalate in Dagestan. It begins by tracing the political history of the Dargin people within the state entities of Caucasian Albania and Shandan. Following Shandan’s collapse, the Dargins settled in their tribal territories, forming small ethno-territorial unions of rural communities. Initially fragmented and under the influence of the Nutsal of Khunzakh, the Dargins achieved unity in the pre-Timur period, securing independence from the Nutsal. By the 15th century, the strengthened Kazikumukh Shamkhalate extended its authority over the Dargins, imposing taxes. In the early 16th century, the Dargins rebelled, gaining political autonomy and forming an alliance with the Shamkhalate. This alliance stipulated that the Akushin Qadi would lead the Dargins and hold the significant privilege of “coronating” new Shamkhals, thereby influencing the succession process. Consequently, Akusha-Dargo emerged as a key player in regional military and political affairs, establishing itself as a formidable state entity in Dagestan. The study reveals that the Shamkhalate, pursuing an active foreign policy, relied on military support from the Akusha-Dargo federation. In return, the Dargins, lacking sufficient winter pastures, leased grazing lands from the Shamkhalate. This mutually beneficial alliance thus facilitated the socio-political and economic development of both entities.